2023
DOI: 10.21203/rs.3.rs-2415228/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of MiR-32 in Chinese Hamster Ovary Cells Increases Production of Fc-fusion Protein

Abstract: The demand for industrial genetically modified host cells has been increased with the growth of the biopharmaceutical market. Numerous studies on improving host cell productivity have shown that altering host cell growth and viability through genetic engineering can increase recombinant protein production. During the last decades, it has been demonstrated that overexpression or downregulation of some microRNAs in Chinese Hamster Ovary (CHO) cells as the most often employed host cell in biopharmaceutical manufa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Namely, let‐7b (common in CHO EVs from stressed cultures) may induce CHO cell apoptosis, while miR‐92a (common in CHO EVs from unstressed, exponential‐phase cultures) may promote CHO cell survival. A more robust study stably overexpressing these miRs in CHO cells will be required to fully understand the role these miRs have on industrially relevant parameters such as cell growth, viability, apoptosis, titer, and product quality (Bazaz et al, 2023; Leroux et al, 2021). Studies have revealed that specific combinations of miRs can result in phenotypic changes (Cursons et al, 2018; Kao et al, 2022), suggesting that the highly abundant miRs identified in CHO EVs may need to be examined in combination to identify any potential phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, let‐7b (common in CHO EVs from stressed cultures) may induce CHO cell apoptosis, while miR‐92a (common in CHO EVs from unstressed, exponential‐phase cultures) may promote CHO cell survival. A more robust study stably overexpressing these miRs in CHO cells will be required to fully understand the role these miRs have on industrially relevant parameters such as cell growth, viability, apoptosis, titer, and product quality (Bazaz et al, 2023; Leroux et al, 2021). Studies have revealed that specific combinations of miRs can result in phenotypic changes (Cursons et al, 2018; Kao et al, 2022), suggesting that the highly abundant miRs identified in CHO EVs may need to be examined in combination to identify any potential phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, let-7b (common in CHO EVs from stressed cultures) may induce CHO cell apoptosis, while miR-92a (common in CHO MPs from unstressed, exponential-phase cultures) may promote CHO cell survival. A more robust study stably overexpressing these miRs in CHO cells will be required to fully understand the role these miRs have on industrially-relevant parameters such as cell growth, viability, apoptosis, titer, and product quality (Bazaz et al, 2023;Leroux et al, 2021). Studies have revealed that specific combinations of miRs can result in phenotypic changes (Cursons et al, 2018;Kao et al, 2022), suggesting that the highly abundant miRs identified in CHO EVs may need to be examined in combination in order to identify any potential phenotypes.…”
Section: Discussionmentioning
confidence: 99%